Gugatan Warga dan Tanggung Jawab Negara dalam Pemenuhan Hak Atas Pendidikan - Ahsri, Muhammad (Indonesian Journal of International Law, 2008)
Right to education, as one of the universe human rights, has been recognized by international community as one of fundamental right. This right brings obligation to government of a State to fulfill education need to its citizens. However, there are problems to fulfill education need. This article tries to examine on how and whether citizens could establish state responsibility in right of education fulfillment. It can be argued that even though the obligation of this right has been changed from “obligation to result” to “obligation to conduct” and it was already maintained by the court, Indonesian citizens are still difficult to obtain their right upon education.